Analisis Nilai Pendidikan Karakter dalam novel 172 Days karya Nadzira Shafa Melalui Pendekatan Hermeneutika Paul Ricouer: Analysis of Character Education Values in the Novel '172 Days' by Nadzira Shafa through Paul Ricoeur’s Hermeneutic Approach - Dini Andiyani; Nuzul Tenriana; Rusman Latif; Imran Imran; Mansur Ga'ga (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to find the character education values in Nadzira Shafa's novel "172 Hari" and understand how these values can impact readers using Paul Ricouer's hermeneutic approach and descriptive design, the novel "172 Hari" was chosen as the subject of qualitative research. Reading and note-taking methods were used to collect information from the text. According to the results, there are fourteen character education values, which include religious, honest, responsible, tolerance, hard work, independent, disciplined, curiosity, brotherhood/communicative, democratic, creative, social care, love of peace, and respect for achievement. Religious values dominate and have a positive impact on readers, such as strengthening spiritual awareness, being an example in facing life's trials, developing noble character, teaching sincerity in accepting destiny, and creating togetherness and brotherhood. It is hoped that this research can deepen the understanding of character values in the novel and contribute to the character formation of readers.